Determinan Pertumbuhan UMKM Lokal: Peran Profitabilitas, Produktivitas, Utang Eksternal, dan Dukungan Pemerintah pada UMKM Product Placement Pilihan BUSAN - Nurullyta Rochmatul Azizah; Verawati Verawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine the effect of profitability, productivity, external debt, and government support on the growth of Micro, Small, and Medium Enterprises (MSMEs) that are part of the BUSAN Product Placement Choice program. The study uses a quantitative approach with multiple linear regression analysis through the help of Stata version 19 software. MSME growth is measured using two approaches: log revenue growth as the main model and percentage growth as a comparison model. Profitability is proxied by Return on Assets (ROA), productivity is measured using a logarithmic transformation of productivity, external debt is measured through the Debt-to-Asset Ratio (DAR), while government support is measured based on MSMEs’ perceptions using a Likert scale. The results of the main model analysis indicate that profitability and productivity have a negative and significant effect on MSME growth. On the other hand, external debt and government support do not show a significant effect. In the comparison model using percentage growth, profitability and productivity are proven to have a negative and significant effect, while external debt and government support still do not show a significant effect on MSME growth.